ASPEK PSIKOLOGIS DAN TRANSAKSI PSIKOLOGIS DUA TOKOH BERSAHABAT NOVEL SOBAT KARYA PUTU WIJAYA - Iswari, Rike Annisa (Humanis, 2013)
Sobat is a novel written by Putu Wijaya which was published by Sinar Harapan. This novel is enriched with psychological aspect and the psychological interaction within the characters. It tells about the conflicts occur in two different families. Two best friends, Aji and Isak have a dominant role in the story. Sobat novel is analyzed using psychological literary approach. Theories that used in this study are the psychoanalytic theory proposed by Sigmund Freud and the theory of transactional psychology proposed by Eric Berne. The psychoanalytic theory is used to analyze the psychological aspect of those two characters. Aji and Isak’s personality consist of the id, ego, superego and the defense mechanism that can’t be separated each other. The transactional psychology is used to find out the process of transaction consists of everyone who involves in it and what message that have been exchanged.
Keywords: Sobat, psychoanalytic, transactional psychology